2007
DOI: 10.1007/s12088-007-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in symbiotic efficiency of chickpea (Cicer arietinum) by coinoculation of Bacillus strains with Mesorhizobium sp. Cicer

Abstract: Rhizobacteria belonging to Bacillus sp. were isolated from the rhizosphere of chickpea (Cicer arietinum). Ten Bacillus strains were studied for their antifungal activity, effect on seedling emergence and plant growth promotion. Two Bacillus strains CBS127 and CBS155 inhibited the growth of all the four pathogenic fungi tested on nutrient agar medium plates in vitro. Seed inoculation with different Bacillus strains showed stimulatory effect on root and shoot growth at 10 d of observation in comparison to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…These results suggest that increase in seed emergence in PGPR treatments might be due to induction of IAA production and phosphate solubilization. These results corroborated with the findings NS -Non significant of Sivaramaiah et al (2007) who also found stimulatory effect on seedling emergence at 10 days with two rhizobacteria Bacillus strains CBS 127 and CBS 155 in chickpea. The same results were reported by Kumar et al (2000) in which seed bacterization with both fluorescent Pseudomonas strains and Rhizobium and their combinations (co-inoculations) brought distinct crop enhancement in pea.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These results suggest that increase in seed emergence in PGPR treatments might be due to induction of IAA production and phosphate solubilization. These results corroborated with the findings NS -Non significant of Sivaramaiah et al (2007) who also found stimulatory effect on seedling emergence at 10 days with two rhizobacteria Bacillus strains CBS 127 and CBS 155 in chickpea. The same results were reported by Kumar et al (2000) in which seed bacterization with both fluorescent Pseudomonas strains and Rhizobium and their combinations (co-inoculations) brought distinct crop enhancement in pea.…”
Section: Resultssupporting
confidence: 90%
“…Maximum height was recorded with Meso+ PGPR 3 in both varieties (20.4 cm in desi PBG 1 and 21.9 cm in kabuli BG1053) followed by Meso + PGPR 2 and Meso+ LK884. This investigation has been found coherent between the result of Sivaramaiah et al (2007) who reported the enhancement in root and shoot length in agar plates at 10 days with Bacillus strains in chickpea. Improvement in plant height with PGPR or Mesorhizobium sp alone or dual over control plants in both varieties of chickpea could be attributed to presence of phytohormone (IAA) which function as signal molecule in the regulation of plant development.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These PGPR improve the plant growth through multitudinous factors viz. production of plant growth promoting substances and hormones (Ahmad et al, 2008;Malik and Sindhu, 2011;Liu et al, 2014), early colonization of root surfaces (Benziri et al, 2001), reducing ethylene level due to synthesis of 1-aminocyclopropane-1-carboxylate (ACC) deaminase (Glick, 2014;Chaudhary and Sindhu, 2015), enhancing the availability of nutrients (Sivaramaiah et al, 2007;Sindhu et al, 2010) and by synthesis of antibiotic and other pathogen-depressing substances such as siderophores, cyanide and hydrolytic enzymes (Voisard et al, 1989;Sindhu and Dadarwal, 2001) and stimulation of phytoalexins/flavonoid-like compounds in roots (Goel et al, 2001). The present study was planned with the objective to evaluate the plant growth promotion ability of different rhizobacterial isolates under chillum jar conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The reports on the efficacy of Bacillus sp. showed enhance nodulation, plant dry matter and grain yield on co-inoculation with Rhizobia in other legumes [33]. Bacterial strains isolated from the maize rhizosphere including Bacillus, Pseudomonas and Serratia were reported to improve the yield by 9-14% [34].…”
Section: Eric Fingerprinting and Survival Efficacy Of Bacterial Strainsmentioning
confidence: 99%